Interacting with patients at risk of self-harm or suicide - A qualitative study of community pharmacists and pharmacy staff - Michelle O'Driscoll; Cian O'Mahony; Eve Keating; Niamh O'Regan; Laura J. Sahm (Elsevier, 2023)
Background: Suicide and self-harm are significant public health concerns. Community pharmacies are accessible and frequented regularly by the public, making them well positioned to identify and intervene with those at risk. The aims of this research project are to evaluate pharmacy staff experiences of dealing with people at risk of suicide/self-harm, and explore how best to support staff during these interactions. Methods: Semi-structured online and telephone interviews were conducted with a sample of community pharmacists and community pharmacy staff (CPS) in the south west of Ireland. Interviews were audio recorded and transcribed verbatim. The Braun and Clarke approach to inductive thematic analysis was used to analyse the data. Results: Thirteen semi-structured qualitative interviews were conducted in November-December 2021. Most participants had encountered a person at risk of suicide/self-harm in their practice, however participants described a lack of training and guidelines around how to navigate these scenarios. Three major themes emerged: (i) Interacting with patients at risk of suicide/self-harm- facilitators and barriers; (ii) Referrals and signposting; (iii) Addressing uncertainty. Positive relationships between the person and pharmacy staff facilitated interactions, while privacy, time constraints and uncertainty among staff were seen as barriers. Participants felt it was necessary to refer at-risk people to other supports, and made suggestions for increasing staff confidence through the implementation of support tools within the pharmacy setting. Conclusions: This study highlights that at present, community pharmacy staff feel uncertain regarding how to handle interactions with people at risk of suicide/self-harm, due to lack of training and supports. Future research should focus on building upon existing resources and obtaining specialist and stakeholder input to produce the most effective support tool(s), tailored to the pharmacy setting.